PREVALENCE, INTENSITY AND ECOLOGICAL ASPECTS OF CONTRACAECUM SP. (NEMATODE: ANISAKIDAE) IN FRESHWATER FISH OF ARGENTINA - Mancini, Miguel A. (2014)
The genus Contracaecum belongs to the Anisakidae family which includes parasites of considerable economic and medical importance. Larvae of Contracaecum are associated with a wide variety of freshwater and marine fish. Although there are a significant number of reports that indicate the presence of anisakid in fish from different parts of the world, there are few studies in the central region of Argentina, despite the prevalence observed in recent years. In the present study we provide new records and analyze ecological aspects of anisakid from fish of different aquatic systems with different hydrological characteristics from central Argentina.Atotal of 1402 individuals belonging to nine species, six families and four orders of fish were examinated for nematode parasites. The helminths were found in Astyanax eigenmanniorum (Characidae), Oligosarcus jenynsii (Characidae), Odontesthes bonariensis (Atherinopsidae), Hoplias malabaricus (Erythrinidae), Pimelodus albicans (Pimelodidae) and Rhamdia quelen (Pimelodidae). The last three host species showed up to 100% prevalence and maximum intensities of 162, 180 and 48 larvae/fish, respectively. All parasites found coincide with larvae of Contracaecum sp. type 2.